Transformasi Wahhabisme di Era Visi 2030: Adaptasi Agama dalam Dinamika Politik Arab Saudi - Farah Farouk Alwyni; Mohammad Izdiyan Muttaqin (Spektrum, 2026)
The transformation of Wahhabism in Saudi Arabia within the framework of Vision 2030 reflects a fundamental shift in the relationship between religion, state, and society. Although Wahhabism has historically served as the ideological foundation of the Saudi kingdom since the 18th century, the modernization policies promoted by Crown Prince Mohammed bin Salman have systematically pushed for a reformulation of this doctrine. This study adopts a qualitative approach using literature review methods to analyze the state's strategies in reconstructing Wahhabism and their socio-political implications. The primary focus includes the redefinition of religious discourse, co-optation of the clerical establishment, and the deconstruction of Wahhabi symbols in public spaces. Moreover, the study highlights the impact of these changes on the legitimacy of political power, the role of clerics, and the relationship between religion and the state. Utilizing institutional and discourse analysis frameworks, this research finds that the state is not only reshaping internal ideological structures but is also repositioning religion as a tool for development and social control. The findings indicate a shift from religion-based legitimacy to performance-based legitimacy, alongside the marginalization of independent clerics and the institutionalization of a more pragmatic, state-defined version of Islam.